2015
DOI: 10.1039/c4cc05639f
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin derivatives as potent and selective blockers of neuronal Kv1 channels

Abstract: Selective inhibitors of voltage-activated K(+) channels are needed for the treatment of multiple sclerosis. In this work it was discovered that porphyrins bearing 2-4 carbon alkyl ammonium side chains predominantly blocked the Kv1.1 current whilst Kv1.2 was susceptible to a porphyrin bearing polyamine side chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…In designing selective blockers, their size and hydrophobicity are vital criteria because, if made too small, they would enter deep into the inner pore region, which is conserved in all K + channels and, similar to 4-aminopyridine (4-AP), selectivity would be lost. Although we have reported that various substituted porphyrin derivatives are selective blockers of neuronal Kv1 channels 19 due to their phototoxicity and high molecular weights, these are nonideal therapeutic candidates. 25 However, informed by structure−activity relationships of the porphyrins and using molecular modeling, valuable pharmacophore information was realized that afforded the development of a more suitable lead structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In designing selective blockers, their size and hydrophobicity are vital criteria because, if made too small, they would enter deep into the inner pore region, which is conserved in all K + channels and, similar to 4-aminopyridine (4-AP), selectivity would be lost. Although we have reported that various substituted porphyrin derivatives are selective blockers of neuronal Kv1 channels 19 due to their phototoxicity and high molecular weights, these are nonideal therapeutic candidates. 25 However, informed by structure−activity relationships of the porphyrins and using molecular modeling, valuable pharmacophore information was realized that afforded the development of a more suitable lead structure.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 We recently reported that four porphyrin derivatives with different alkyl ammonium side chains (in length and geometry) inhibit Kv1.1 and/or 1.2 channels expressed in mammalian cells. 19 Now, a new generation based on diaryldi-(2-pyrrolyl) methane (DPM) is described with various substitutions bearing alkyl ammonium side-chains, which have been screened against recombinantly generated Kv1 channels of known subunit structures. The resultant data were used to design the novel small inhibitor 2,2′-((5,5′-(di-p-topyldiaryldi(2-pyrrolyl)methane)bis(2,2′-carbonyl)bis(azanediyl))diethaneamine• 2HCl (8), which proved selective for Kv1.1-containing channels found in rodent demyelinated axons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The manganese porphyrin compounds 1 (Mn-porphyrin) was synthesized following the reported literature with some modifications [ 34 ]. Tetrakis (4-carboxyphenyl) porphyrin (TCPP, 94 mg) was mixed with EDCI (143 mg) and NHS (90 mg) in DMF and then stirred under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…H2tcpp was prepared according to literature methods. 7 A round-bottom flask was charged with 4-carboxybenzaldehyde (1.54 g, 0.0103 mol, 1.02 equiv) and propanoic acid (50 mL). The reaction mixture was heated to 80 °C until 4-carboxybenzaldehyde was completely dissolved.…”
Section: Synthesis Of 5101520-tetrakis(4-carboxyphenyl)porphyrin (mentioning
confidence: 99%